Are there Gender Differences in Diabetes Care Among Elderly Medicare Enrolled Veterans? - Tseng, Chin-Lin (Blackwell Science Inc, 2006)
OBJECTIVE: To examine gender differences in diabetes care process measures and intermediate outcomes among veteran clinic users. DESIGN: A retrospective cohort study using Veterans Health Administration (VHA) and Medicare files of VHA clinic users with diabetes. Diabetes care process measures were tests for hemoglobin A1c (HbA1c), low-density lipoprotein (LDL-C) values, and eye exams. Intermediate outcomes were HbA1c and LDL-C values below recommended thresholds. Chi-square tests and logistic regressions were used to assess gender differences. PARTICIPANTS: Study population included 3,225 women and 231,922 men veterans with diabetes, enrolled in Medicare fee-for-service and alive at the end of fiscal year 2000. RESULTS: Overall, there were no significant gender differences in HbA1c or LDL-C testing. However, women had higher rates in these process measures than men among the non-African American minorities. Women were more likely to have completed eye exams (odds ratio [OR]=1.11; 99% confidence interval [CI]=1.10, 1.23) but were less likely to have LDL-C under 130 mg/dL (OR=0.77; 99% CI=0.69, 0.87). CONCLUSIONS: Among VHA patients with diabetes, clinically significant gender inequality was not apparent in most of diabetes care measures. However, there was evidence of better care among nonwhite and non-African American women than their male counterparts. Further research on interaction of race and gender on diabetes care is needed. This includes evaluation of integrated VHA women's health programs as well as cultural issues. Lower LDL-C control among women suggests areas of unmet needs for women and opportunities for future targeted quality improvement interventions at system and provider levels.